Electricity market clearing for multiple stakeholders based on the Stackelberg game - Wu, Xuguang; Ye, Qingquan; Chen, Liyuan; Liao, Hongtu; Wang, Wanhuan (Frontiers in Energy Research, 2024)
In order to improve the operating benefits of the distribution network and reduce the energy consumption costs of small–micro-industrial parks, an electricity market clearing considering small–micro-industrial parks is proposed based on the Stackelberg game. First, an optimal operating model of multiple stakeholders is established for integrated energy suppliers, the electricity market, and small–micro-industrial parks. In this model, an optimal electricity supply model for integrated energy suppliers is established with the goal of maximizing the operating benefits. A market clearing optimization model is established for the electricity market with the goal of maximizing the social surplus profit. In addition, an energy utilization optimization model is established for the small–micro-industrial parks with the goal of minimizing the energy procurement costs. Second, with the electricity market as the leader, the integrated energy suppliers and the small–micro-industrial parks as the followers, a leader–follower game strategy is proposed based on the Stackelberg game theory to achieve the maximizing benefits for multiple stakeholders. Finally, the simulation indicates that the proposed strategy can find the best profit point during the game process and achieve a balance between supply and demand.